Multimodal Analgesia for Acute Postoperative and Trauma-Related Pain. Issue 3 (March 2017) - Polomano, Rosemary C.; Fillman, Mechele; Giordano, Nicholas A.; Vallerand, April Hazard; Nicely, Kelly L. Wiltse; Jungquist, Carla R.
Abstract : N/A: Multimodal analgesia, which combines analgesic drugs from different classes and employs analgesic techniques that target different mechanisms of pain, is recommended in the treatment of acute postoperative and trauma-related pain because its synergistic effect maximizes pain relief at lower analgesic doses, thereby reducing the risk of adverse drug effects. Using a case-based approach, this article reviews various multimodal analgesic therapies used in the treatment of acute pain; discusses their benefits; and summarizes findings from related research, recommendations from evidence-based practice guidelines, and expert consensus reports.